Peran Media Sosial Instagram Sebagai Sarana Kampanye dalam Strategi Komunikasi Politik - Suryasuciramdhan, Arfian; Zulfikar, Meiby; Fajarwati, Noerma Kurnia; Hakim, Cecep Abdul; Arasid, Mohamad Ikrom (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
The role of social media which has a big role in political communication strategies for voter participation and how the relevance of political communication is increasing on social media platforms, implies the development and change of traditional political communication by converging information technology with more modern political communication so as to achieve novelty much more effectively to interact with the community. This research uses qualitative methods with descriptive narratives aimed at providing explanatory results that are easy to understand by describing and understanding social phenomena from the perspective of the subject under study. Subjects in research are individuals involved in the object of research based on information and data. The use of social media platforms can be systematically planned and programmed to develop identity politics, it is important to ensure interactive interactions on social media platforms. It is concluded that social media can be a forum as well as a facilitator and play a role for an interest and has the potential to have benefits in political campaigns. Through platforms such as Twitter, Instagram and TikTok political candidates can interact with the public and successfully win the hearts of the people.